Design and FEA Verification of Flexure Hinge for a Precision Platform - Chang Xu; Gao Sitian; Li Dongsheng; Li Qi; Shi Yushu; Qian Xiaoli (Jixie chuandong)
The precision platform is a kind of high precision working platform which can provide the micrometer displacement. In precision platform design,flexible hinge structure is widely used as mechanism of transmission. The flexible hinge plays the key role in determining the performance of the platform,the structure shape and size parameters of the flexible hinge affect the positioning accuracy. A novel flexible hinge structure constructed by superimposed branched chain is described,and the working stiffness,coupling stiffness,coupling coefficient as well as hinge stress performance of the platform based on this flexible hinge are calculated.In order to testify the accuracy of the results,finite element analysis software is utilized to cross validation. At last,it is showed that both the calculation and the simulation results have good consistency,which provides a reference for the design of flexure hinge used in precision platform.